Insect pest in rice field with legumes embankment applied by Beauveria bassiana vuill. Issue 2 (July 2021) - Fitri,; Aminah, S N; Abdullah, T; Widarawati, R; Annisa, N W
Abstract: The objectives of research is to determine the diversity of insect pests in rice fields and the effect of B. bassiana spraying around the ecosystem. The collection and observation of pest populations in rice and legumes embankments was held in Mappadaelo village, Tanasitolo District, Wajo Regency, South Sulawesi. Experiments used Mekongga rice varieties in four different fields with a distance between rice fields of around 200 - 300 m. Legumes in the embankment was planted a week after planting rice, the types of legumes: green beans, long beans and cowpeas. The research used Randomized Block Design eight treatment and four replication. Observation of pest insect of rice started from 14 days after planting used ten sample of legume plant in embankment (five samples legumes without B. bassiana spraying and five samples of plants sprayed B. bassiana ). The insects were collected on the embankment used D-Vac, then the sample put in a bottle contain alcohol 70%. The interval collected sample used D-Vac was seven days. The results was showed the diversity of insect pests in rice field without spraying B. bassiana was 2.48 with the highest diversity index in treatment P1 of 0.71. The lowest insect diversity index on plants in rice field without B. bassiana spray as P3 treatment of 0.65. The diversity of pest insect in rice fields sprayed with B. bassiana was 2.28. The highest diversity index was found in treatment P7 of 0.75. The lowest insect diversity index in rice fields sprayed with B. bassiana was treatment P6 of 0.45. The conclusion of the study spraying the entomopathogenic fungi B. bassiana affected the diversity index of pest insect attacked rice plant.